A role and value of record-keeping in the system of the informative providing of investment acti vity - Яфонкін, Анатолій Олексійович; Яфонкіна, Юлія Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article are considered questions of role and value of record-keeping in the system of theinformative providing of investment activity, high-quality descriptions of information of-position of decision-making, the analysis of legislation is conducted, touching accounting and current information.